Adenosine A2A receptors in the rostral ventrolateral medulla participate in blood pressure decrease with electroacupuncture in hypertensive rats - Guo, Zhi-Ling; Tjen-A-Looi, Stephanie C.; Nguyen, Anh Thingoc; Fu, Liang-Wu; Su, Hou-Fen; Gong, Yiwei D.; Malik, Shaista (Frontiers in Cardiovascular Medicine, 2023)
Acupuncture is increasingly used to manage high blood pressure (BP) as a complementary therapy. However, the mechanisms underlying its hypotensive effects remain unclear. Our previous studies have shown that electroacupuncture (EA) at the ST36-37 acupoints, overlying the deep peroneal nerve, attenuates pressor responses through adenosine A2A receptors (A2AR) in the rostral ventrolateral medulla (rVLM). However, it is uncertain whether rVLM A2AR contributes to EA's BP-lowering effect in sustained hypertension. We hypothesized that a course of EA treatment lowers BP, in part, through the activation of adenosine A2AR in the rVLM in hypertensive rats. To mimic essential hypertension in the clinic, we performed EA in conscious Dahl salt-sensitive hypertensive rats (DSHRs). EA (0.1–0.4 mA, 2 Hz) was applied at ST36-37 for 30 min twice weekly for four weeks, while sham-EA was conducted in a similar manner but without electrical input. In hypertensive rats, BP was reduced by EA (n = 14) but neither by sham-EA (n = 14) nor in the absence of needling (n = 8). Following four weeks of eight treatments and then under anesthesia, EA's modulatory effect on elevated BP was reversed by unilateral rVLM microinjection of SCH 58261 (1 mM in 50 nl; an A2AR antagonist; n = 7; P < 0.05) but not the vehicle (n = 5) in EA-treated DSHRs. Activation of rVLM A2AR in DSHRs treated with sham-EA by an A2AR agonist, CGS-21680 (0.4 mM in 50 nl; n = 8), decreased BP. Unilateral administration of SCH 58261 or CGS-21680 into the rVLM did not alter basal BP in Dahl salt-sensitive rats fed a regular diet with normal BP. The A2AR level in the rVLM after EA was increased compared to the sham-EA and untreated DSHRs (n = 5 in each group; all P < 0.05). These data suggest that a 4-week twice weekly EA treatment reduced BP in salt-sensitive hypertensive rats likely through adenosine-mediated A2AR in the rVLM.